A Study of Women in R.K. Narayan’s ‘The Guide’ and Chinua Achebe’s ‘Things Fall Apart’ - et. al., K. Rita Josephine Eve , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the paper is study the portrayal of women in R.K.Narayan’s ‘The Guide’ and Chinua Achebe’s ‘Things Fall Apart’ Literature is often said to be a reflection of society. So based on the theory of social realism, a study is done on the realistic portrayal of women in the above mentioned works. It is necessary to also identify the conditions, the factors in the environment that affects the characters. A study has been made upon the women seen in the novel and an attempt to comprehend why they behave the way they do. Steps are taken to identify the conditions prevalent and the expectations of society in regard to women. An insight has also made into the empowerment factor of these women.